PENDIDIKAN AGAMA KATOLIK BAGI ANAK BISU DAN TULI - Sofiarti, Melania Safirista; Gaudiawan, Antonius Virdei Eresto (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2021)
Mute and deaf children are also part of the Church which also has the right to catholic religious education. Therefore, this research was carried out in an attempt to answer several questions: what is catholic religious education? What is the situation of mute and deaf students? How is catholic education for children mute and deaf?. This research was conducted at SLB Hellen Keller Yogyakarta, SLB Dena Upakara Wonosobo, and SLB Bhakti Luhur Madiun. The respondents of this study are catholic religious teachers who taught mute and deaf children. Catholic religious education must be mute and deaf children. Basically, from the cognitive point of view, they are just like children listening, except that the limitations in language make them also limited in catching material. Related to that, it was proposed to develop methods, media, and teachers in catholic religious education, so that the Christian faith of mute and deaf children became deeper and more practical in daily life.